Giant Pyogenic Granuloma in the Palmar Area [Botriomicoma Gigante de Localización Palmar] - Cardemil-Van Der Schraft, A; Segovia-Gonzalez, L; Loubies-Muñoz, R (Ediciones Doyma, S.L., 2017)
Sin Resumen Disponible